2022
DOI: 10.1161/hypertensionaha.122.19222
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Control Among US Adults, 2009 to 2012 Through 2017 to 2020

Abstract: Background: The National Health and Nutrition Examination Survey data indicate that the proportion of US adults with hypertension that had controlled blood pressure (BP) declined from 2013 to 2014 through 2017 to 2018. We analyzed data from National Health and Nutrition Examination Survey 2009 to 2012, 2013 to 2016, and 2017 to 2020 to confirm this finding. Methods: Hypertension was defined as systolic BP ≥140 mm Hg or diastolic BP ≥90 mm Hg or antihype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 45 publications
5
71
0
Order By: Relevance
“…1,2 This condition has been subjected to intensive study for over half a century leading to the development of a variety of classes of pharmaceutical options to lower blood pressure; however, fewer than 50% of patients achieve good blood pressure control. 3 Further confounding clinical treatment of hypertension is the multifactorial dysfunctional aspect of this disease wherein an estimated 90% -95% of treated patients present with unclear origin (essential hypertension), 4 and an estimated 20-30% of cases are resistant to currently available treatment (resistant hypertension). 5 Thus, it is important to investigate unknown mechanisms causing essential hypertension and develop new therapeutic strategies against hypertension.…”
mentioning
confidence: 99%
“…1,2 This condition has been subjected to intensive study for over half a century leading to the development of a variety of classes of pharmaceutical options to lower blood pressure; however, fewer than 50% of patients achieve good blood pressure control. 3 Further confounding clinical treatment of hypertension is the multifactorial dysfunctional aspect of this disease wherein an estimated 90% -95% of treated patients present with unclear origin (essential hypertension), 4 and an estimated 20-30% of cases are resistant to currently available treatment (resistant hypertension). 5 Thus, it is important to investigate unknown mechanisms causing essential hypertension and develop new therapeutic strategies against hypertension.…”
mentioning
confidence: 99%
“… 5–8 29–32 For example, one study used National Health and Nutrition Examination Survey data to demonstrate decline in achievement of blood pressure targets in the 2017–2020 period versus 2009–2012 among women and black adults. 31 Another study observed larger declines in HbA1c testing among females with DM (vs males) but this was associated with higher rebound in testing after lockdown. 7 While we did not directly model rebound testing, we indirectly captured it through measuring outcomes at an annual scale.…”
Section: Discussionmentioning
confidence: 96%
“…Hypertension (HTN) is a major cause of death and disability worldwide, and a leading risk factor for dementia 1 . Although there have been significant advances in the pharmacotherapy, a sizable proportion of patients have uncontrolled or resistant HTN which is particularly damaging to the brain 2, 3 . Furthermore, despite suggestive evidence that a rigorous control of blood pressure (BP) may lower the risk of mild cognitive impairment 4 , the burden of HTN on the brain remains substantial, including a 10% risk of recurrent cerebrovascular events despite BP control and no proven strategy to prevent dementia 5 .…”
Section: Introductionmentioning
confidence: 99%